1996
DOI: 10.1002/pssb.2221930207
|View full text |Cite
|
Sign up to set email alerts
|

On the pressure dependence of the Grüneisen parameter and debye temperature for CsI crystals

Abstract: An analysis of the pressure dependence of the Griineisen parameter y and the Debye temperature 8 for CsI based on the model developed by Kumari and Dass is presented. From the pressure dependence of the recoilless fraction behaviour y is deduced which shows that y varies linearly with pressure as y ( p , T ) = yoyp, where q is found to be pressure independent. 8 ( p ) also displays a linear variation with p , which is consistent with the recoilless fraction behaviour of y-ray emission or absorption in the Moss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…[4], the tests on four solids (NaCl, Li, Na, and K) have shown that the calculated results given by the nonlinear (6) agrees with the experimental data on the pressure dependence of g better than the results given by the linear relation (3) through an improved value of h was used in (3). Especially in the case of NaCl the results of g at high pressures given by (6) are more reasonable than those given by (3).…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…[4], the tests on four solids (NaCl, Li, Na, and K) have shown that the calculated results given by the nonlinear (6) agrees with the experimental data on the pressure dependence of g better than the results given by the linear relation (3) through an improved value of h was used in (3). Especially in the case of NaCl the results of g at high pressures given by (6) are more reasonable than those given by (3).…”
Section: Discussionmentioning
confidence: 47%
“…In the case of CsI, the experimental data of both the Debye temperature and the Gru È neisen parameter are available [6,7]. With Eq.…”
Section: Theory and Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…20 On the other hand, for a series of polyamides at room temperature, eq 5b gave: c G ¼ 0.45 to 0.64. 14 Its magnitude was found increasing with T and decreases with P. [21][22][23] The diversity of Grüneisen parameter values originates from the applied methods of measurements, calculation procedures, and extension of the original concept to polyatomic substances having a variety of morphologies.…”
mentioning
confidence: 99%